Complaint Management System for Sarawak Rural Area Water Supply Department - Selina, Luat (UNIMAS Publisher, 2021)
This Complaint Management System is developed to manage the complaints received by the Corporate Communication Unit of the Sarawak Rural Area Water Supply Department. This system was developed to solve the current problems faced in managing, retrieving and updating data using the manual method by the Department. Users of the system are the administrative staff and division water engineers. Users are able to add, update and delete complaint records, as well as view information in graphical format such as pie charts and graphs. Rapid Application Development (RAD) was used to develop this system, consisting of four phases: analysing user requirement, develop a prototype, construction and cut over. The feedback received from the Department’s staff is positive and showed that the users are satisfied with the system developed.